2018
DOI: 10.1002/chem.201800600
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Multinuclear Complexes Incorporating 99mTc

Abstract: Multinuclear complexes or clusters are rarely investigated in medicinal inorganic chemistry although they represent structural intermediates between molecules and nanomaterials. We present in this report two strategies towards Tc-containing clusters. In a pre-assembly approach, the preformed but incomplete cluster fragment [Re (μ -OH) (μ -OH)(CO) ] reacts with [ Tc(CO) ] to the highly stable [ TcRe (μ -OH) (CO) ] cube. The same structure self-assembles when reacting the mononuclear Re and Tc precursors in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Reactionof1 + + (Re) and 1 + + ( 99m Tc )w ith 2-mercapto-ethanol yields the dinuclear heterometallic (Re/ 99m Tc )complex 2 À À (top). HPLC traces of 2 À À (g-detection,red trace, R t = 18.6 min) and Re 2 (m 2 -S(CH 2 ) 2 OH) 3 (CO) 6 ] À (UV-detection, black trace, R t = 17.7 min)c onfirm the structurali dentity of the two homologues. The signals at longer retention times are complexes of higher nuclearity.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Reactionof1 + + (Re) and 1 + + ( 99m Tc )w ith 2-mercapto-ethanol yields the dinuclear heterometallic (Re/ 99m Tc )complex 2 À À (top). HPLC traces of 2 À À (g-detection,red trace, R t = 18.6 min) and Re 2 (m 2 -S(CH 2 ) 2 OH) 3 (CO) 6 ] À (UV-detection, black trace, R t = 17.7 min)c onfirm the structurali dentity of the two homologues. The signals at longer retention times are complexes of higher nuclearity.…”
mentioning
confidence: 76%
“…We recently showed that multinuclear complexes comprising one 99m Tc moiety are accessible either by a pre‐ or a self‐assembly approach . Extending this concept from oxygen‐ to sulfur bridging ligands, we found that [Re(OH 2 ) 3 (CO) 3 ] + ( 1 + (Re)) together with [ 99m Tc(OH 2 ) 3 (CO) 3 ] + ( 1 + ( 99m Tc)) and 2‐mercaptoethanol HS(CH 2 ) 2 OH rapidly led to quantitative consumption of 1 + ( 99m Tc) and the formation of 2 − as the major product (Figure , top), besides higher molecular clusters as minor products.…”
Section: Figurementioning
confidence: 98%
See 2 more Smart Citations
“…This has been followed by two strategies which can prepare multinuclear rhenium(I) and technetium(I) tricarbonyl complexes, either di-or tetranuclear clusters, in a one-pot reaction. Furthermore, it allows for a tetranuclear cluster containing both rhenium and technetium metal centres to be a model theranostic agent (Frei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%